ปัจจัยส่งผลต่อผลผลิตงานวิจัยของอาจารย์มหาวิทยาลัยนเรศวร: Factors Affecting Research Productivity of Instructors in Naresuan University - Sutthi, Supajuck; Parnichparinchai, Teamjan (Asian Health, Science and Technology Reports, 2011)
The objectives of this research were as follows: (1) to study the research productivity of instructors in Naresuan University, (2) to study level of opinion about impact factors which affect to research productivity of Naresuan University instructors (3) to study correlation between factors and research productivity of Naresuan University instructors (4) to find the best affecting factors on research productivity of Naresuan University instructors. This study performed by the 870-instructors who hold a chief position of research project and got supporting budget both within the university and other sources in academic year 2009. Questionnaire was used for data collection and the data were analyzed by SPSS for windows. The statistics for data analysis were frequency, percentage, mean, standard deviation and multiple regression analysis. The results of this research revealed as follows: 1. most researchers in Naresuan University have research output per budget year can be divided into two categories: (1) for single research found that 28.67% was completed and 15.40% is on process, (2) for team research found that 35.31% was completed and 20.62% is on process. The research experience both single and team research equal 68.49%. For only single research experience equal 21.29% and only team research experience equal 9.25%. 2. in general, the level of opinion about impact factors with affect to research productivity of Naresuan University instructors revealed a high level ( = 3.84). When considered in each facet, the study found the level of opinion have mean between 3.24 - 4.32. The highest mean was responsibility in research ( = 4.32), attitudes toward research ( = 4.15), knowledge on research distribution ( = 4.10), respectfulness from public ( = 4.03), and the least mean was time and responsibility ( = 3.24). 3. the correlation between affecting factors and research productivity of Naresuan University instructors found that the predictor variables were single and team research experience, attitudes toward research, supporting documents and facilities, time and responsibility, and ability in research distribution significantly statistical difference at the level of .05 4. the best affecting factors on research productivity of Naresuan University instructors revealed significantly statistical difference at the level of .05 were experience of both single and team research, knowledge on research distribution, document and supporting instrument for research, attitude toward on research, respectfulness from public, and field of research in sciences and technology. All those factors can predict research productivity of Naresuan University instructors which have power of forecasting equal 26.10%